The effects of chronic, dose-dependent administration of dronedarone and amiodarone on cardiodynamics and oxidative stress parameters of isolated rat heart with hypertension. (19th May 2022) - Simovic, S; Jeremic, J; Srejovic, I; Davidovic, G; Zivkovic, V; Mitrovic, S; Nikolic, M; Ravic, M; Andjic, M; Rankovic, M; Draginic, N; Jakovljevic, V
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Amiodarone represents the most widely used antiarrhythmic drug with an indication for administration in heart failure (HF) with many of its side effects. Dronedarone reduces the risk of recurrent atrial fibrillation, with increased mortality due to worsening HF, but necessary experimental data is missing. Purpose: Investigate chronic, dose-dependent effects of Dronedarone and Amiodarone on cardiodynamic and oxidative stress of spontaneusly hypertensive rat (SHR) heart. Methods: The present study was carried out on 42 SHR Wistar Kyoto male rats: Control (n=6), and 6 experimental groups treated by oral lavage for 4 weeks: rats treated with 100 mg/kg of Amiodarone (n=6), rats treated with 50 mg/kg of Amiodarone (n=6), rats treated with 10 mg/kg of Amiodarone (n=6), rats treated with 50 mg/kg of Dronedarone (n=6), rats treated with 10 mg/kg of Dronedarone (n=6) and rats treated with 5 mg/kg of Dronedarone (n=6). Isolated rat hearts were perfused by Langendorff perfusion apparatus and following cardiodynamic parameters were continuously registered: dp/dt max, dp/dt min, systolic left ventricular pressure, diastolic left ventricular pressure, heart rate and coronary flow on each of predetermined values of coronary perfused pressure. Parameters of oxidative stress were determined spectrophotometrically. Results: Amiodarone in the low dose significantly improved dp/dt max and dt/dt min, this effect was less pronounced in the middle dose of Amiodarone, while Amiodarone in the high dose significantly decreased all parameters of cardiac function. Amiodarone in low dose significantly increased levels of parameters of oxidative stress including levels of O2- and nitrites, when compared to other doses of Amiodarone. Significant changes in cardiac function were also observed in Dronedarone treated rats, however function was significantly decreased in all Dronedarone groups. Dronedarone severely depressed cardiac function with dose-dependent effect. Comparison between Amiodarone and Dronedarone groups revealed that Amiodarone was better in improvement of cardiac function in all dose-regimes (Figure 1). Dronedarone significantly lowered levels of H2O2 and TBARS without dose-dependent effect, concentrations of O2-, NO2- remained unchanged. Amiodarone increased O2-, NO2- and TBARS with a dose-dependent effect. When compared to Amiodarone, Dronedarone lowered all oxidative stress parameters in high, middle and low-dose (Figure 2.) Conclusion: Dose-dependent, chronic administration of Dronedarone severely depressed SHR cardiac function. Amiodarone shows less pronaunced effects in high and middle dose, while low dose increased cardiac function. By comparing the effects of Amiodarone and Dronedarone, Amiodarone showed better effects on SHR cardiac function in all doses, while Dronedarone significantly reduced parameters of oxidative stress in all doses, when compared to their parallel doses of Amiodarone.